9 - A New Learning Experience of Training in the Social Sciences Using Online Platforms in Low-Resource Settings: A Pandemic Experience at Busitema University, Uganda - Alice Nakiyemba,; Musobya Moses,; Masaba Sowedi, (CODESRIA Bulletin, 2023)